Impact of metagenomic sequencing on clinical outcomes in patients with suspected central nervous system infections: a retrospective case-control study - An, Wenyan; Zhang, Yandong; Liu, Yong; Yang, Tianshi; Bai, Shiqi; Zhou, Peiwen; Si, Junzhuo; Zhao, Yuan; He, Yulu; Pan, Yijia; Jiang, Yanfang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesAlthough the value of metagenomic sequencing (mNGS) in diagnosing pathogens in central nervous system infections (CNSi) has been confirmed, its impact on the clinical outcomes of patients remains to be elucidated. This study intended to investigate the clinical impact of cerebrospinal fluid (CSF) mNGS on the outcomes of patients with suspected CNSi.MethodsBetween January 2022 and July 2024, patients who met both the inclusion and exclusion criteria were enrolled in the study and assigned to either the mNGS group (CSF tested by both mNGS and conventional microbiological tests [CMTs]) or the CMT group (CMTs alone). Following this, propensity score matching (PSM) was applied to balance baseline differences. The primary endpoint, time to clinical improvement, was then compared between the two groups and analyzed in stratified subgroups. Secondary endpoints included the rates of clinical improvement at 14 and 30 days, hospital stay, in-hospital mortality, and the proportion of GCS score <15.ResultsA retrospective analysis of 338 patients was conducted, with 169 cases in each group. In the mNGS group, a comparison of diagnostic performance between the two testing methods demonstrated that mNGS yielded a significantly higher positivity rate in patients with CNSi compared to CMTs (67.5% vs. 18.3%, p < 0.001), identifying 111 pathogens in total, which was substantially more than the 24 detected by CMTs. Subsequent comparison of clinical outcomes between the groups showed that the duration until clinical improvement was significantly reduced in the mNGS group when compared to the CMT group (median: 14 days vs. 17 days; p=0.032). Moreover, a significantly higher percentage of patients in the mNGS group experienced clinical improvement within 14 days compared to those in the CMT group(42.6% vs. 31.4%; p=0.032). Subgroup analysis further revealed that the mNGS group’s superiority in clinical improvement over the CMT group was only evident in patients with CNSi, especially when complicated by pneumonia.ConclusionThe combination of mNGS with CMT significantly improves the clinical outcome of CNSi patients, offering greater clinical utility than traditional methods alone.